Identification of Ants (Hymenoptera: Formicidae) in Urban Manila, Philippines Through DNA Barcoding - Anthony Ian G. Pag-ong; Dulce Marie P. Nisperos; Rodante G. Flores (East Asian Journal of Multidisciplinary Research, 2023)
Urbanization is a driving force behind habitat destruction and has a dramatic impact on ant richness and composition. This ecological and taxonomic study of urban ants generally focused on identifying species richness in different urban habitat types using DNA barcoding techniques. 17 species of ants collected from Manila, Philippines were sequenced and barcoded for a 600 – 700 range bp region of the mitochondrial cytochrome c oxidase subunit 1 gene (CO1). The AT content in the DNA of 16 ant species was estimated at 68.5%, which is following invertebrates. The distance within species was calculated using the Kimura 2-parameter (K2P) and it was 0.244, 0.168, and 0.331% for mean, minimum, and maximum, respectively. The phylogeny tree constructed using the N-J method also revealed two clusters. The first cluster consisted of three sub-clades representing four subfamilies: Myrmicinae, Ponerinae, while Pseudomyrmicinae, and Dolichoderinae are within the same sub-clade but with different sub-group. The second cluster is formed by the sub-clades of the Formicinae subfamily, which is not in contradiction with the cladistics analysis of morphological data for ants and is consistent with the traditional phylogeny. The results demonstrate that DNA barcoding is an additional tool for providing pertinent information for the systematist for quick and reliable identification of urban ants.